(untitled) (Journal of the Bangladesh Agricultural University, 2018)
The study examined the performance of Faro 44 improved rice variety in increasing rice production in Niger State, Nigeria. To achieve the objectives of the study, 203 farmers were randomly selected from three Local Government Areas in the State. Validated interview schedule with reliability co-efficient of 0.89 was used for collecting data and collected data were analyzed using descriptive statistics and Pearson’s Product Moment Correlation analysis. The result indicated that the mean age of the respondents was 43 years, with mean farm size of 2.1ha. Finding also revealed that a total 97.54% of the respondents adopted Faro 44 improved rice variety in their farms. The mean yield of the respondents was 6 Tons/ha., which increased the rice output of more than half (52.22%) of the respondents twice. The mean income was N675, 000.00 ( 1,824.32); this led to empowerment of the respondents in the areas of attending to family welfare needs (89.66%), re-investment in farming businesses (70.94%) and acquisition of landed properties (50.73%). Challenges of adoption were complexity of some components of improved variety (39.90%) and late delivery of improved seeds (35.47%). The result further showed that respondent’s educational level (r = 0.285), farm size (r = 0.309) and extension contacts (r = 0.236) had significant relationship with adoption of improved rice variety. Thus, it was recommended that extension service providers should provide follow-up information to the farmers to educate them more on the agronomic practices of the improved rice variety. It was also suggested that back-up inputs such as improved seeds should be made available to farmers adequately and on time by relevant stakeholders. J. Bangladesh Agril. Univ. 16(2): 182-186, August 2018